Empirical essays on the effectiveness of active labor market policies: Caseworkers, vocational training & statistical profiling - Mette Buskjær Rasmussen (University of Copenhagen, Department of Economics, 2021)
How do policy makers help jobseekers transition out of unemployment? As unemployment is costly for the individual and inefficient for society, this is a question of utmost importance. Today, many OECD countries rely on active labor market policies (ALMPs) in their efforts to easen jobseekers' transitions out of unemployment and improve their subsequent labor market performance. Public expenditures on these policies are substantial. In 2017, the average OECD country spent about 0.5% of GDP on ALMPs, and Denmark was in the top with expenditures amounting to about 2%. Policy makers have a wide range of active labor market policies at their disposal, e.g. job search assistance and training facilitated through regular meetings with a caseworker. In order to chose the policies optimally, it is important to know what policies work best and for whom. This PhD dissertation consists of three self-contained chapters that all study how different types of active labor market policies can help unemployed jobseekers transition out of unemployment. All three chapters rely on novel data provided by the Danish Agency for Labor Market and Recruitment.
Keywords: 330; Arbeitsmarktintegration; Arbeitsmarktpolitik; Erfolgsfaktor; OECD-Staaten